IMPLEMENTASI PROGRAM TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN DALAM MENDUKUNG PENGEMBANGAN USAHA MIKRO KECIL SUPPLY CHAIN DI PT PLN (PERSERO) PUSHARLIS - Ghitha Zahirah Fasya; Chandra Hendriyani; Fenny Damayanti (POLITEKNIK LP3I JAKARTA, 2023)
Business continuity is highly dependent on a harmonious relationship between the company and its supporting ecosystem such as employees, customers and the environment. To support this, the company must implement a Social and Environmental Responsibility (TJSL) program. The purpose of implementing the TJSL program is to contribute to the development of micro and small businesses or local communities. PT PLN (Persero) Pusharlis has a TJSL priority on the economic pillar through the development of the UMK Supply Chain which is in line with the 2030 Sustainable Development Goals (SDGs) goals of reducing poverty, unemployment, and improving people's welfare. This study uses a qualitative method with a descriptive approach to data collection techniques through interviews and literature studies. The object of research is CV Karya Mandiri Manufacture which is a fostered partner of PT PLN (Persero) Pusharlis which has succeeded in increasing production requests by 75 requests from the previous 50, resulting in an increase in employment of 22.2%. Thus it can be concluded that the TJSL program at PT PLN (Persero) Pusharlis was able to increase economic growth and absorb labor in the MSE Supply Chain. Key words: Social and Environmental Responsibility, TJSL, MSE, Supply Chain